Mixed mode fracture behaviour of steel fibre reinforced concrete - Ng, T.; Foster, S.; Htet, M.; Htut, Trevor (2014)
In this paper, results are reported for a series of discrete end hooked and straight fibre pullout tests subjected to mixed mode action with the results compared to that of discrete fibres pulled out in Mode I (tensile) and Mode II (shear) fracture. As has been previously observed from Modes I and II fracture tests, the snubbing effect dominates the behaviour of fibres at large fibre bending angles. At large fibre bending angles, considerable slip and crack separation occurred prior to the fibres being engaged in taking load and fibres that are inclined close to the cracked surface are ineffective in carrying load. The results of the test were compared with the fibre engagement and bond stress models in the Unified Variable Engage- ment Model (UVEM). A good correlation is observed for the UVEM model with the test data and provides further confirmation of the validity of the UVEM model to predict the mix mode fracture of steel fibre reinforced concrete.